INTENTION TO PURCHASE VIA THE INTERNET: A COMPARISON OF TWO THEORETICAL MODELS - Jasman J. Ma'ruf,; Osman Mohamad,; T. Ramayah, (Asian Academy of Management Journal, 2005)
This study compares two models for predicting intention to purchase via the Internet. The behavioral intention to purchase via the Internet was examined as a function of attitude towards purchase, perceived usefulness, and perceived ease of use Technology Acceptance Model (TAM), or attitude towards purchase, subjective norm, and perceived risk (Theory of Planned Behavior [TPB]). Results indicate that both models significantly influenced behavioral intention to purchase. We compared both models, and found that TPB (adjusted R² = 0.55) is better than TAM (0.44) in explaining behavioral intention to purchase (BI). After we integrated TAM and TPB, we found that perceived risk (? = –0.332) is the primary determinant of BI, with subjective norm (SN) (? = 0.210) as the significant secondary determinant, followed by attitude (A) towards purchase (? = 0.175), perceived usefulness (? = 0.159), and perceived ease of use (? = 0.069).